SELFÃ¢â¬âACTUALIZATION OF HUMANÃ¢â¬â¢S NEEDS: THE PORTRAIT OF A WOMANÃ¢â¬â¢S STRUGGLE AGAINST PATRIARCHY IN NH. DINIÃ¢â¬â¢S NOVEL BANDUNGAN STREET - Asianti, Dwi Anggara (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2010)
Patriarchy places Mur, the main character in NH DiniÃ¢â¬â¢ s novel entitled Ã¢â¬ÅBandungan StreetÃ¢â¬Â, as the secondary citizen, since its orientation is men. This condition impedes her to reach MaslowÃ¢â¬â¢s hierarchy of needs. The apathy and sadness come since those needs cannot be met. It prompted her to be powerless. Then, she uses the Ã¢â¬ËWill to PowerÃ¢â¬Â proposed by Nietzsche as to control the undesired condition to empower herself. At last, she can achieve self-actualization, to be the best she can be, as the highest needÃ¢â¬â¢s rank. It proves that women can even be the better species if they are also given the same opportunity. ÃÂ Key words: patriarchy, will to power, self-actualization.